Effects of rare-earth size on the electronic structure of La1−xLuxVO3. (24th February 2015) - Chen, B; Laverock, J; Newby, D; McNulty, J F; Smith, K E; Glans, P-A; Guo, J-H; Qiao, R-M; Yang, W-L; Lees, M R; Tung, L D; Singh, R P; et al.
Abstract: The electronic structure of La1− x Lu x VO3 ( x  = 0, 0.2, 0.6 and 1) single crystals has been investigated using soft x-ray absorption spectroscopy, soft x-ray emission spectroscopy, and resonant soft x-ray inelastic scattering to study the effects of rare-earth size. The x-ray absorption and emission spectra at the O K -edge present a progressive evolution with R -site cation, in agreement with local spin density approximation calculations. This evolution with R, together with the temperature dependence of the O K -edge spectra, is attributed to changes in the crystal structure of La1− x Lu x VO3 . The crystal-field dd * excitations probed by resonant inelastic x-ray scattering at the V L 3 -edge exhibit an increase in energy and enhanced intensity with the decrease of R -site ionic radius, which is mainly attributed to the increased tilting magnitude of the VO6 octahedra. Upon cooling to ∼95 K, the dd * excitations are prominently enhanced in relative intensity, in agreement with the formation of the Jahn–Teller distortion in the orbital ordering phase. Additionally, the dd * transitions of the mixed compounds are noticeably suppressed with respect to those of the pure compounds, possibly owing to the formation of C -type orbital ordering induced by large R -site size variances.